Walt Whitman Among the French : Poet and Myth. - Erkkila, Betsy (Princeton legacy library., 2014)
As the first full treatment of Walt Whitman's French sources and his later impact on French writers, this book revises our image of the poet and challenges many critical assumptions. Originally published in 1980. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is t.